Disinhibition of Primitive Reflexes in Attention Deficit and Hyperactivity Disorder: Insight Into Specific Mechanisms in Girls and Boys - Bob, Petr; Konicarova, Jana; Raboch, Jiri (Frontiers in Psychiatry, 2021)
Objective: Cognitive and motor disintegration and other functional disturbances in various neuropsychiatric disorders may be related to inhibitory deficits that may manifest as a persistence or re-expression of primitive reflexes and few recent data suggest that these deficits may occur in Attention Deficit and Hyperactivity Disorder (ADHD). Methods: We have tested a hypothesis to which extent ADHD symptoms and balance deficits are related to persisting primitive reflexes, such as Asymmetric Tonic Neck Reflex (ATNR) and Symmetric Tonic Neck Reflex (STNR) in 80 medication-naïve children with ADHD (40 boys and 40 girls) in the school age (8-11 years) and compared these data with a control group of 60 children (30 boys and 30 girls). Results: These data show new finding that ADHD symptoms and balance deficits are strongly and specifically associated with persistent ATNR in girls and STNR in boys. Conclusions: These results provide first evidence in medical literature that ADHD in girls and boys is specifically related to distinguished neurological developmental mechanisms related to disinhibition of primitive reflexes.